PENGARUH PERSEPSI PEMILIK ATAS TUJUAN LAPORAN KEUANGAN DAN PEMAHAMAN AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN UMKM (Studi pada UMKM di Kecamatan Cikarang Utara) - Dhevindy Damayanti; Lasmini, Lilis; Septiawati, Rohma (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2023)
This research aims to examine the influence of owner perceptions of the purpose of financial reports and understanding of accounting on the quality of MSME financial reports (study of MSMEs in North Cikarang District). The population in this study was 172 MSMEs in North Cikarang District. The sampling technique used in this research was a random sampling technique, with a sample of 120 respondents determined using the Slovin formula. The subjects of this research are MSMEs in North Cikarang District. Data collection uses a questionnaire, to analyze the relationship between variables using IBM SPSS 26. The results of the research show that the owner's perception of the purpose of financial reports and understanding of accounting influence the quality of financial reports.